PENGARUH MENTAL TOUGHNESS DAN COMPETENCY TERHADAP ORGANIZATIONAL COMMITMENT DIMEDIASI OLEH JOB SATISFACTION PADA KARYAWAN GEN Z DI JAKARTA - Ratri Ayu Asmorofitri; Irma Febri Damayanti; Netania Emilisa; Diajeng Athahira Ramadhanti (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This research focuses on the influence of Mental Toughness and Competence on Organizational Commitment mediated by Job Satisfaction by conducting studies on Generation Z employees which are still limited. This research was conducted by means of hypothesis testing (hypothesis testing) which was used to test the influence of Mental Toughness and Competence on Organizational Commitment and Job Satisfaction as mediation for Gen Z Employees in Jakarta. The type of relationship between variables used is correlation research because it explains the variables related to the problem. The data used is cross sectional because it will only be conducted once in a certain period and the unit of analysis is individuals, namely Gen Z employees in Jakarta. The research setting used is a non-contrived setting because the research was conducted where work is generally located. The results of descriptive statistics show that Gen Z employees feel Mental Toughness in Gen Z employees in Jakarta. Employees who have Mental Toughness will often receive appreciation for their ability to manage stress more effectively and remain calm when facing difficult situations at work.